Mesenchymal Stem Cells and COVID-19: Cure, Prevention, and Vaccination - Mehrdad Afarid; Fatemeh Sanie-Jahromi (Stem Cells International)
COVID-19 disease has been a global health problem since late 2019. There are many concerns about the rapid spread of this disease, and yet, there is no approved treatment for COVID-19. Several biological interventions have been under study recently to investigate efficient treatment for this viral disease. Besides, many efforts have been made to find a safe way to prevent and vaccinate people against COVID-19 disease. In severe cases, patients suffer from acute respiratory distress syndrome usually associated with an increased level of inflammatory cytokines, called a cytokine storm. It seems that reequilibrating the hyperinflammatory response of the host immune system and regeneration of damaged cells could be the main way to manage the disease. Mesenchymal stem cells (MSCs) have been recently under investigation in this regard, and the achieved clinical outcomes show promising evidence for stem cell-based therapy of COVID-19. MSCs are known for their potential for immunomodulation, defense against virus infection, and tissue regeneration. MSCs are a newly emerged platform for designing vaccines and show promising evidence in this area. In the present study, we provided a thorough research study on the most recent clinical studies based on stem cells in the treatment of COVID-19 while introducing stem cell exclusivities for use as an immune disorder or lung cell therapy and its potential application for protection and vaccination against COVID-19.